1997
DOI: 10.1111/j.1600-0560.1997.tb01319.x
|View full text |Cite
|
Sign up to set email alerts
|

p53 and bcl‐2 expression do not correlate with prognosis in primary cutaneous large T‐cell lymphomas

Abstract: Overexpression of p53 protein in cutaneous T‐cell lymphoma (CTCL) has been reported in primary cutaneous large T‐cell lymphomas (PCLTCL) and has been associated with tumor progression and transformation in mycosis fungoides. However, the prognostic significance of p53 expression has not been studied thus far. In the present study we investigated the expression of p53 as well as bcl‐2 protein in 27 PCLTCL, including 19 CD30‐positive and 8 CD30‐negative lymphomas, retrieved from the registry of the Dutch Cutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…Well-known tumor suppressor genes such as tumor protein 53 (P53; 17p13.1) and CT-10 regulator of kinase (CRK; 17p13.1) are encoded in this region. Similar to our chromosomal findings, a study of P53 expression in CTCL did not find a correlation with prognosis (van Haselen et al, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…Well-known tumor suppressor genes such as tumor protein 53 (P53; 17p13.1) and CT-10 regulator of kinase (CRK; 17p13.1) are encoded in this region. Similar to our chromosomal findings, a study of P53 expression in CTCL did not find a correlation with prognosis (van Haselen et al, 1997).…”
Section: Discussionsupporting
confidence: 88%
“…41 Our findings showed that p53 was detected by immunohistochemistry in 9/45 cases (20 per cent), while molecular analysis did not show the presence of mutations in exons 4-8 in any of these cases. These results are not substantially different from those of Matsushima et al on HTLV-1-negative post-thymic T-cell lymphomas 37 or those of de Misa et al, 38 Marks et al, 39 and Van Haselen et al 40 on cutaneous T-cell lymphomas, indicating altogether that p53 is detectable by immunohistochemistry in 20-50 per cent of PTCL cases. Since p53 expression is rarely due to mutation, this presumably reflects an abnormality of the functional pathway of p53, resulting in the accumulation (or stabilization) of a wild-type protein, which then becomes detectable by immunohistochemical analysis.…”
Section: Discussionmentioning
confidence: 40%
“…[38][39][40] Conversely, p53 mutations seem to be more frequent in HTLV-1-positive adult T-cell leukaemia/lymphoma. 41 Our findings showed that p53 was detected by immunohistochemistry in 9/45 cases (20 per cent), while molecular analysis did not show the presence of mutations in exons 4-8 in any of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…The classical cell cycle-control gene p53 has been reported to be overexpressed in late stages of CTCL, that is, during large-cell transition [4][5][6][7]. However, the importance of this finding for the prognosis is controversial [8].…”
Section: Introductionmentioning
confidence: 99%